Media representations of opposition to the 'junk food advertising ban' on the Transport for London (TfL) network: A thematic content analysis of UK news and trade press. (September 2021) - Thompson, Claire; Clary, Christelle; Er, Vanessa; Adams, Jean; Boyland, Emma; Burgoine, Thomas; Cornelsen, Laura; de Vocht, Frank; Egan, Matt; Lake, Amelia A.; Lock, Karen; Mytton, Oliver; et al.
Abstract: Background: Advertising of less healthy foods and drinks is hypothesised to be associated with obesity in adults and children. In February 2019, Transport for London implemented restrictions on advertisements for foods and beverages high in fat, salt or sugar across its network as part of a city-wide strategy to tackle childhood obesity. The policy was extensively debated in the press. This paper identifies arguments for and against the restrictions. Focusing on arguments against the restrictions, it then goes on to deconstruct the discursive strategies underpinning them. Methods: A qualitative thematic content analysis of media coverage of the restrictions (the 'ban') in UK newspapers and trade press was followed by a document analysis of arguments against the ban. A search period of March 1, 2018 to May 31, 2019 covered: (i) the launch of the public consultation on the ban in May 2018; (ii) the announcement of the ban in November 2018; and (iii) its implementation in February 2019. A systematic search of printed and online publications in English distributed in the UK or published on UK-specific websites identified 152 articles. Results: Arguments in favour of the ban focused on inequalities and childhood obesity. Arguments against the ban centred on two claims: that childhood obesity was not the 'right' priority; and that an advertising ban was not an effective way to address childhood obesity. These claims were justified via three discursive approaches: (i) claiming more 'important' priorities for action; (ii) disputing the science behind the ban; (iii) emphasising potential financial costs of the ban. Conclusion: The discursive tactics used in media sources to argue against the ban draw on frames widely used by unhealthy commodities industries in response to structural public health interventions. Our analyses highlight the need for interventions to be framed in ways that can pre-emptively counter common criticisms. Highlights: The first analysis of news coverage of regulation of food advertisements on public transport. Arguments against the ban claimed childhood obesity was not a valid priority and restricting advertising was ill advised. Public health interventions need to be framed in ways that can pre-emptively counter opposition.